Pentachlorophenol removal from aqueous matrices by sorption with almond shell residues - B.N. Estevinho (2006)
Sorption with activated carbon has been the technique preferred for pentachlorophenol (PCP) removal from contaminated waters, but regeneration needs and high operation costs are supporting a renewed interest in the search for alternative sorbents. Among them, almond shell, an agricultural by-product, provides interesting economical advantages, once shells account for 50% (in mass) of the whole almond. In this work, the capacity of almond shells to remove PCP from waters without previous activation was studied in batch conditions. While PCP analysis was performed solid-phase microextraction (SPME) followed by gas chromatography with electron capture detection (GC-ECD), mercury porosimetry and Fourier transform infrared spectroscopy (FTIR) provided a preliminary physical and chemical characterization of the sorbent. Almond shells were essentially a macroporous material, with an average surface area of 12.9 +/- 2.8 m(2)/g. The efficiency of PCP removal was 93 +/- 14%, in 24 h, with an initial concentration of 100 mu g/l PCP and 5 mu g PCP/g shell. Isotherm data adjusted better to Freundlich equation, where K-F and 1/n were 0.075 +/- 0.081 mg(1-1/n) 1(1/n) and 1.882 +/- 10.289, respectively. Average desorption efficiency was 7%, indicating strong adsorption capacity. Results proved that almond shells may be an excellent low-cost alternative for PCP removal from contaminated waters.